Evaluation of Pigmentary Keratitis in Pugs: A Study on Prevalence and Corneal Pigmentation Patterns - Rajasekaran Tiruppur Manikumar; Shashi Kant Mahajan; Nameirakpam Umeshwori Devi; Jasmeet Singh Khosa; Arun Anand (Archives of Current Research International, 2025)
Aim: To study the clinical occurrence and pattern of pigmentary keratitis (PK) in pugs. Place and Duration of Study: Department of Veterinary Surgery and Radiology, College of Veterinary Science, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana, Punjab, India during the year 2020-21. Methodology: This study was conducted on 200 eyes of hundred Pug breed of dogs presented for non-ocular conditions to study the prevalence of PK. Digital photographs of the eyes were used to study and score the corneal pigmentation (CP) and classify them into various patterns based on a previously established grading system. Results: CP was detected in a total of 96 Pugs (192 eyes) in the study population with a mean age of 5.27±0.29 years. The severity of pigmentation was mild for 15.10%, moderate for 39.58% and severe for 45.31% with their mean pigmentation score being 2.98±0.21, 6.89±0.18, and 13.35±0.16 respectively. Detection of PK was not significantly associated with the sex, coat colour or the side of the eye, but was significantly associated (P < 0.05) with the age of the animal. The severity of CP and the pattern of pigmentation were not significantly associated with the coat colour or the side of the eye, but were significantly associated with the age and sex of the animal. Conclusion: PK showed a higher prevalence among the study population, and the age and sex of the animals can be used as reliable predictors of the score of CP in Pugs.